ANALYSIS OF THE IJARAH CONTRACT IN THE PRACTICE OF RENTING RICE FIELDS: A CASE STUDY IN NORTH KLUET DISTRICT, SOUTH ACEH REGENCY - Iqbal, Muhammad; Leili, Putri (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
In North Kluet Subdistrict, South Aceh District, the farming community, rice fields become objects of rent for the benefit of cultivation so as to obtain crops for living needs. The purpose of this research is to find out the risk coverage of rice field crop failure and the payment mechanism, the forms of rental risk coverage at the time of crop failure to the parties, and the perspective of the ijarah contract on the risk coverage of rice field rental in North Kluet District, South Aceh Regency. This research uses a normative sociological approach and descriptive qualitative research analysis with data collection techniques through interviews/interviews, observation, and documentation data. The results showed that among the farming community of North Kluet Sub-district, South Aceh District, the risk coverage for the lease of paddy fields is carried out at the time of the lease agreement. At the time of the lease transaction, the owner of the paddy field will explain the condition of the land and the yields that are usually achieved, the payment of the rental of paddy fields is made when the harvest period is completed by the farmer with the same rental price as the previous harvest or raised slightly above the previous rent, with an explanation of the consequences of renting land, such as crop failure and others. For the case of crop failure, the parties agree on the consequences of crop failure either due to lack of water, pests, and force majeure then the solution offered that the losses incurred including all operational costs will be borne by the tenant, but the one who bears a lot of losses here is the land tenant even though the owner of the rice field also shares the loss because the rental price is adjusted to income by putting forward the principle of ‘mutual understanding’ due to lack of yield or crop failure, and payment of land rental prices will differ in amount from the initial lease agreement. The application of the lease of paddy fields among the people of North Kluet District, South Aceh Regency is not in accordance with Islamic law, because the tenant must work on it first and then get the results, and the results obtained are also not benefits.